2007
DOI: 10.1063/1.2732167
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear excitation of geodesic acoustic modes by drift waves

Abstract: In this paper, two mode-coupling analyses for the nonlinear excitation of the geodesic acoustic modes (GAMs) in tokamak plasmas by drift waves are presented. The first approach is a coherent parametric process, which leads to a three-wave resonant interaction. This investigation allows for the drift waves and the GAMs to have comparable scales. The second approach uses the wave-kinetic equations for the drift waves, which then couples to the GAMs. This requires that the GAM scale length be large compared to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
95
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 69 publications
(104 citation statements)
references
References 19 publications
9
95
0
Order By: Relevance
“…There is much linear study on GAM's damping due to collision and ion Landau resonance [8][9][10][11][12][13][14][15][16] and on GAM's radial propagation due to finite thermal ion gyroradius and plasma temperature profile inhomogeneity [13,14]. Nonlinear studies found that that GAM can be driven by plasma microturbulence [13,[17][18][19], consistent with experimental observation of GAM in the plasma edge region [20][21][22]. Recently, Sasaki et al showed that self-interaction of turbulence-induced GAMs can drive both second harmonic [23] and zonal flow sideband [24].…”
Section: Introductionmentioning
confidence: 99%
“…There is much linear study on GAM's damping due to collision and ion Landau resonance [8][9][10][11][12][13][14][15][16] and on GAM's radial propagation due to finite thermal ion gyroradius and plasma temperature profile inhomogeneity [13,14]. Nonlinear studies found that that GAM can be driven by plasma microturbulence [13,[17][18][19], consistent with experimental observation of GAM in the plasma edge region [20][21][22]. Recently, Sasaki et al showed that self-interaction of turbulence-induced GAMs can drive both second harmonic [23] and zonal flow sideband [24].…”
Section: Introductionmentioning
confidence: 99%
“…As shown in earlier work, 12 the dominant nonlinear coupling is to the primary mode m 0 = n / q, where q is the safety factor at the rational surface. There are couplings to the m 0 Ϯ 1 sidebands, which turn out to be 1 / m 0 smaller than the dominant terms.…”
Section: Basic Finite ␤ Equationsmentioning
confidence: 99%
“…9,10 The second class of modes near the GAM frequency are observed in the edge region of tokamaks by a variety of diagnostic methods, and these are believed to be excited by nonlinear processes. [11][12][13] In this study we will focus on the nonlinear type of excitation and extend our earlier work by including finite beta effects.…”
Section: Introductionmentioning
confidence: 99%
“…There is much linear study on GAM's damping due to collision and ion Landau resonance [8][9][10][11][12][13][14][15][16] and on GAM's radial propagation due to finite thermal ion gyroradius and plasma temperature profile inhomogeneity [13,14]. Nonlinear studies found that that GAM can be driven by plasma microturbulence [13,[17][18][19], consistent with experimental observation of GAM in the plasma edge region [20][21][22]. Recently, Sasaki et al showed that self-interaction of turbulence-induced GAMs can drive both second harmonic [23] and zonal flow sideband [24].…”
Section: Introductionmentioning
confidence: 99%